E-Sport and Taxes. Selected Issues - Michał Biliński (Financial Law Review, 2022)
The article presents reflections on several selected issues of tax law that occur in the area of a new and emerging field of the so-called e-sport. Firstly, the features of such activity were analyzed and the question whether it could be classified within the concept of sport was answered. Next, the affirmative conclusion allowed for the consideration of a number of dilemmas related to the choice of the correct tax regime for income obtained in the sphere of professional gaming.